Handbook on Research Assessment in the Social Sciences - Engels, Tim C. E.; Kulczycki, Emanuel (Cheltenham, UK: Massachusetts, USA: Edward Elgar Publishing, 2022)
This Handbook provides a comprehensive overview of current developments, issues and good practices regarding assessment in social science research. It pays particular attention to the challenges in evaluation policies in the social sciences, as well as to the specificities of publishing in the area. The Handbook discusses the current societal challenges facing researchers, from digital societies, to climate change and sustainability, to trust in democratic societies. Chapters provide ways to strengthen research assessment in the social sciences for the better, by offering a diverse range of experiences and views of experts from all continents. The Handbook also outlines major data sources that can be used to assess social sciences research, as well as looking at key dimensions of research quality in the social sciences including journal peer review, the issue of identifying research quality, and gender disparities in social science research.This book will be an essential read for scholars interested in research assessment in the social sciences. It will also be useful to policy makers looking to understand the key position of the social sciences in science and society and provide appropriate frameworks for key societal challenges.
Includes bibliographical references and index.
Keywords: Social sciences -- Research; Research -- Evaluation